The factors affecting self-regulation through the analysis of physiological, psychological and behavioural measures during task-switching - Chaplin, Caley (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2013)
Individuals are required to manage multiple tasks which require strategic allocation of time and effort to ensure goals are reached efficiently. By providing the worker with autonomy over their work, performance and worker well-being have improved. This increased control allows individuals to organize work according to the needs of the body, which prevents fatigue leading to improved productivity. When given the option, humans tend to switch between tasks frequently. This behaviour can be used to determine the change in self-regulation strategies. An understanding of human task-switching behaviour is important for the design of job rotation systems. However, there is a lack of evidence explaining the factors motivating the need to switch between tasks. This study aims to use physiological, subjective and behavioural measures to explain the factors influencing selfregulation through the act of task-switching. Three primary hypotheses were developed to explain the factors underlying taskswitching behaviour. It was hypothesized that the degree of boredom experienced, the effort required to perform the task and the resource usage induced by the task are factors responsible in deciding task switching behaviour. Participants (17 males and 17 females) switched freely between five different information-processing tasks for the 45 minutes. Participants were allowed to switch back and forth between tasks and did not have to conduct all five tasks. The following measures were recorded during the experiment: subjective measures of boredom, mental effort, task frustration and perceived performance of the tasks; energy consumption and physiological measures of effort (HR, HRV and body temperature) and behavioural measures, including duration and frequency of task. Perceived boredom was found to differ among the tasks and before and after the experiment. The average boredom rating at each task transition for all tasks exceeded a score of 2.5 out of a possible 4. There were no significant changes in physiological measures between the beginning and end of the task trials. However, changes in physiological measures showed a decrease in effort investment following task transition. Heart rate variability was lower for externally-paced tasks than for self-paced tasks, despite the differences in cognitive demands. The most frequent task-switch combination occurred between tasks of high and low cognitive demand. The least frequent task-switching combination occurred between tasks of similar characteristics, which produced no differences in physiological responses. Task-switching behaviour was influenced by the degree of boredom, and therefore more time was spent on less monotonous tasks. The level of physiological effort required for the task affected task-switching behaviour. Task switches were made before any changes in effort took place in an attempt to maintain task efficiency. It appears plausible that a task switch was made to reduce effort investment and activation levels. The type of information processing resources used by different tasks affected the task-switching combinations. Individuals tended to switch between tasks of differing resources so that those in limited supply were able to replenish. Therefore the findings from this study can potentially be used to improve the design of job rotation systems. Such improvements may enhance productivity and worker well-being by inhibiting the onset of down regulation and fatigue processes. This study showed that autonomy is necessary for individuals to regulate behaviour to suit human needs.,Microsoftï¿½ Office Word 2007,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Human multitasking -- Physiological aspects; Human multitasking -- Psychological aspects; Fatigue; Boredom; Attention; Mental fatigue; Human information processing; Decision making; Labor productivity; Industrial hygiene; Employees -- Workload